PENGARUH KONSEP HANDS-ON DISPLAY TOKO TERHADAP STORE REPATRONAGE INTENTIONS (STUDI KASUS PADA KONSUMEN TOKO SEVEN MART WAINGAPU) - Rambu Yetti Kalaway; Anderias Kopa Rehi (JURNAL TRANSFORMATIF UNKRISWINA SUMBA, 2019)
Hands-on display concept is described by visual communication, store layout, and store display variables. This research focus is to see the implementation of hands-on display on store and the impact to store repatronage intentions. Seven Mart store is used as a research object. Data collection technique use likert scale questionnaire and with purposive sampling method resulted 100 respondents who ever shopped in Seven Mart store. The result shows that there is positive and significant influence between hands-on display on store repatronage intentions.